2020
DOI: 10.3389/fmed.2020.00218
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between FDG Hotspots on Pre-radiotherapy PET/CT and Areas of HNSCC Local Relapse: Impact of Treatment Position and Images Registration Method

Abstract: position. Comparison of registration method demonstrated OF and A X nR X /R X indices (x = 30% to 50%SUVmax) were significantly higher with ER vs. RR in NTP (p < 0.03), but not in TP. For patient position, the OF and A X nR X /R X indices were higher in TP than in NTP when RR was used with a trend toward significance, particularly for x=40%SUVmax (0.50±0.22 vs. 0.31 ± 0.13, p = 0.094). Conclusion:Our study suggested that PET/CT acquired in TP improves results in the localization of FDG hotspots in HNSCC. If TP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In a recent study including 71 HNSCC recurrences, Truffault et al showed a real benefit in the elastic registration of images especially when patients were not scanned in treatment position (NTP). Thus, using the 40%SUVmax method, the OF (A40nR40) of MTVs was significantly higher after ER than RR (p < 0.03) (46,47).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In a recent study including 71 HNSCC recurrences, Truffault et al showed a real benefit in the elastic registration of images especially when patients were not scanned in treatment position (NTP). Thus, using the 40%SUVmax method, the OF (A40nR40) of MTVs was significantly higher after ER than RR (p < 0.03) (46,47).…”
Section: Discussionmentioning
confidence: 89%
“…In the previous mentioned "hotspot" study, Truffault et al also showed an impact in performing pre-and post-therapeutic PET scans in the treatment position (TP) to improve the intersection between MTVs. Thus, OF (A40nR40) changed from low to moderate agreement, increasing from 0.31 ± 0.13 (NTP) to 0.50 ± 0.22 (TP) with a trend toward significance (p = 0.094) (46). On the contrary, the average DICE index evolved from strong to moderate agreement in our subgroup of MTV < 5cc, in particular with PET-Edge method (DICE = 0.44 ± 0.13).…”
Section: Discussionmentioning
confidence: 94%
“…The authors concluded that similarity between FDG hotspot on PET A and areas of local recurrence on PET R showed good to excellent agreement (ranging from 0.60 to 0.93) for lung, esophageal, and rectal carcinomas. They highlighted lower agreement for head and neck cancer, weight loss and tissue distortion after RT-CT affecting the anatomical landmarks and increasing the risk of mis-registrations [45], even if PET A and PET B were acquired in the same position and registered with an elastic method [46]. Nevertheless, no studies were reported on HGG.…”
Section: Discussionmentioning
confidence: 99%
“…82 Truffault et al stated that the tumour localization of hot spot uptake on PET-CT can predict local relapse of HNSCC. 83 Sensitivity and specificity of PET imaging for detecting OMs may be optimized further, for example by utilization of disease-specific radiotracers directed against tumour specific antigens. For example, 18Ffluorodihydrotestosterone, a radio-labelled dihydrotestosterone analogue, directly targets the androgen receptor on tumour cells.…”
Section: Early Screening and Detection Of Omsmentioning
confidence: 99%
“…Truffault et al . stated that the tumour localization of hot spot uptake on PET‐CT can predict local relapse of HNSCC 83 . Sensitivity and specificity of PET imaging for detecting OMs may be optimized further, for example by utilization of disease‐specific radiotracers directed against tumour specific antigens.…”
Section: Early Screening and Detection Of Omsmentioning
confidence: 99%